Autophagy and Exercise: Current Insights and Future Research Directions - Botella, Javier; Shaw, Christopher S; Bishop, David J (International Journal of Sports Medicine, 2023)
Autophagy is a cellular process by which proteins and organelles are degraded inside the lysosome. Exercise is known to influence the regulation of autophagy in skeletal muscle. However, as gold standard techniques to assess autophagy flux in vivo are restricted to animal research, important gaps remain in our understanding of how exercise influences autophagy activity in humans. Using available datasets, we show how the gene expression profile of autophagy receptors and ATG8 family members differ between human and mouse skeletal muscle, providing a potential explanation for their differing exercise-induced autophagy responses. Furthermore, we provide a comprehensive view of autophagy regulation following exercise in humans by summarizing human transcriptomic and phosphoproteomic datasets that provide novel targets of potential relevance. These newly identified phosphorylation sites may provide an explanation as to why both endurance and resistance exercise lead to an exercise-induced reduction in LC3B-II, while possibly divergently regulating autophagy receptors, and, potentially, autophagy flux. We also provide recommendations to use ex vivo autophagy flux assays to better understand the influence of exercise, and other stimuli, on autophagy regulation in humans. This review provides a critical overview of the field and directs researchers towards novel research areas that will improve our understanding of autophagy regulation following exercise in humans.
Keywords: autophagy; LC3; autophagosome; exercise; training; skeletal muscle